The problem of marital violence in Mitchells Plain and its implications for the future of society - Lawrence, Merlyn Judy (Department of Sociology, 2025)
This dissertation examines the corresponding symbols and imagery in N. P. van Wyk Lauw' s "Groot Ode" and DIE HEENGAANREFREIN by Wi Ima Stockenstrbm. The poetic approach in both works is similar and comparable, because both poets are concerned with mankind's questing nature. In both texts man is portrayed as searching for omnipotence through omniscience. A section of the analysis is devoted to extra-textual influences on the two works. Examples of these are: genre expectations, poetic influence and the fact DIE HEENGAANREFREIN was commissioned for a special celebration. Previous analyses are also discussed briefly. The two main sections of this dissertation are ?edicated to analysing the para 11e1 ( 1) images and ( 2) motifs. The simi 1 ar i ties in the application of mirror and colour imagery are but two examples of corresponding threads in both works. Motifs are discussed as the organic entities of a text: they develop in the text and are not the stagnant components that images are. Themes of evolution and of the apocalypse are examples of motifs covered. Language as motif is very important in this analysis, because it is not only an intra-textual occurrence, but also becomes an extra-textual determination. The last section is concerned with the role that language plays ·in ordering the chaos of the universe. The anxiety that the poet experiences as ephebe/successor to God and to earlier poets is also briefly discussed.